An Inquiry On The Changing Face Of Organizational Culture In The Days Of The Pandemic - Hasan Tutar; Nuran Öztürk Başpınar; Selçuk Nam (Akademik İncelemeler Dergisi)
Organizational culture tries to understand human behavior by analyzing thoughts, attitudes, and behaviors. The main purpose of research on organizational culture is to understand organizational functioning and organizational behavior better. The main purpose of this study is to examine the experiences of faculty members working at a state university regarding the changes in organizational culture during the pandemic process. It is qualitative research in terms of research method, and the case study design, one of the qualitative research designs, was used in the research. The research was carried out with a study group of 16 academics and administrative staff working in different units of universities. Observation and semi-structured interview techniques were used as data collection tools in the research. The collected data were analyzed with the transfer of observations and qualitative content analysis. According to the analysis findings, the participants' opinions on the change in organizational ethnography during the pandemic process indicate a significant change in this process's organizational attitudes and behaviors. Analysis findings reveal that a traumatic change such as a pandemic causes various uncertainties and resistances in the organizational field. It is understood that organizational support is essential for constructing a flexible organizational culture suitable for the conditions of this process to eliminate job dissatisfaction and loss of motivation caused by the pandemic.